In Vitro Antioxidant and Anticancer Properties of Extracts of Citrus Limon (Lemon) - Sawyerr, E.R. (University of Ghana, 2018)
Cancer is a disease of health concern globally, arising from uncontrolled proliferation of cells. Most drugs used in chemotherapy are derived from plants. Citrus limon (lemon) has been shown to possess significant amounts of anticancer agents. The purpose of this study was to evaluate the antioxidant and anticancer properties of extracts of C. limon. Aqueous extracts of C. limon were prepared using distilled water by heating, filtration and centrifugation. Organic extracts were prepared by cold maceration and rotary evaporation. Antioxidant activity of the extracts was determined using 2, 2-diphenyl-1-picrylhydrazyl (DPPH), Folin Ciocalteau and total flavonoids (Aluminium Chloride) assays. Cytotoxic activities of extracts on prostate cancer (PC3), breast cancer (MCF-7) and normal prostate (PNT2) cell lines were evaluated using the 3-(4, 5-dimethylthiazol-2-yl)- 2, 5-diphenyltetrazolium bromide (MTT) assay. Rind extracts showed high total phenols and flavonoids, ethyl acetate rind extract having the highest total phenols (6415.268 ± 0.0095mg Gallic acid equivalent/100g extract) and petroleum ether rind extract having the highest flavonoid content (2603.025 ± 0.0121mg Quercetin equivalent /100g extract). Rind extracts also showed high total antioxidant content with the ethyl acetate rind extract having strongest activity (EC50 = 0.4 ± 0.02mg/ml) followed by the ethanolic seed extract (EC50 = 1.0 ± 0.1mg/ml). Ethyl acetate rind extract exhibited strongest cytotoxic activity against PC3 cells (IC50 = 99.1 ± 8.4mg/ml) and petroleum ether rind extract showed strongest cytotoxic activity against MCF-7 cells with an IC50 of 384.6 ± 17.1mg/ml. The ethyl acetate rind extract was found to be the most promising anticancer agent for prostate cancer with a selectivity index of 3.70. The results obtained lend support to earlier reports on the antioxidant and anticancer properties of C. limon.
MPhil.
Keywords: In Vitro Antioxidant; Anticancer Properties; Citrus Limon (Lemon)